The Usage of Swear Word in Hollywood Films - Novari, Ari Fajria; Khoerunnisa, Siti Alnida (Journal of English Education Studies, 2022)
Language is used as a means of communication in social intercourse. It can be used to propose one’s ideas, deliver particular messages, and to express emotions. One of many ways of using language is by producing swear word. Swear word is an offensive word which often used to express humiliation, anger and any other tense emotions. This study concerns with the descriptive analysis and function of swear word found in some Hollywood films like Fast and Furious 6, Suicide Squad, Bad Boys II, and Deadpool. This study was aimed at examining the use of swear word in the movies with different topics and characters. The objectives if this study were to find out the how many using swear word in the movies. This study was conducted by descriptive qualitative method. The source of data was transcript the movies.